Innovative Mathematics Learning : Designing Student Worksheet with Augmented Reality with Lempok Durian Context - Yulia Permatasari; Hartatiana Hartatiana; Ambarsari Kusuma Wardani (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2024)
The use of Augmented Reality (AR) in learning can provide an interactive learning experience that can enhance student engagement. This research aims to produce mathematics worksheet using the context of South Sumatra's typical food namely lempok durian in ratio, which is valid, practical, and has a potential effect on the accuracy of the learning outcomes of seventh-grade students in Palembang. This research is research and development with the ADDIE model. (Analysis, Design, Development, Implementation, and Evaluation). Data is collected through lifts, interviews, and quantitatively and qualitatively analyzed tests. The results of the study showed ratio mathematical material using the lempok durians context is valid based on validator assessment with a validity rating of 0.89 including the high validity category, practical based on the elevation of student response with a practicality rating of 4.13 including very practical category, and has potential effects based on learning results of students with a percentage of the potential effect of 82.6% including the very high category. The development of worksheets with Augmented Reality can be implied by being used as a supporting medium in mathematics learning in an effort to improve learning outcomes and student motivation